TAHURA WAN ABDUL RAHMAN ECOTOURISM ON SOCIAL MEDIA - Toni Wijaya; Nanda Utaridah; Agung Wibawa; Fri Rejeki Noviera (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This study aims to analyze the representation of ecotourism of the Wan Abdul Rachman Forest Park (Tahura) on social media as part of a digital communication strategy in developing sustainable ecotourism. The method used is descriptive qualitative with a digital content analysis approach. Data were collected through the Brand24 and Google Trends platforms during the period March to June 2025. The results of the analysis show that mentions of Tahura on social media are still very limited and all come from non-social media such as news portals and scientific repositories. The sentiment that emerged was neutral, without the involvement of influencers or prominent digital campaigns. Meanwhile, Google Trends data shows that search interest in Tahura is very low and was only recorded in Lampung Province, with one spike in searches during the analysis period. This finding reflects that the digital presence of Tahura Wan Abdul Rachman is still minimal, both in the form of social media discussions and online searches, and is not yet widespread geographically.